2000
DOI: 10.1002/hep.510310222
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin preconditioning: A protection against rat hepatic ischemia-reperfusion injury

Abstract: Doxorubicin produces clinically useful responses in a variety of human cancers. However, the toxicity of doxorubicin has limited its usefulness. This side effect is mainly due to the doxorubicin-mediated free radical formation. Administration of doxorubicin (10 mg/kg body weight) to rats intravenously induces heme oxygenase-1 (HO-1) in the liver. The levels of HO-1 protein were first detected at 6 hours and peaked at about 18 to 24 hours after the injection. It is known that HO-1 plays a protective role agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
1
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 27 publications
1
30
1
1
Order By: Relevance
“…In the case of major hepatectomy performed under inflow occlusion, the technique of ischemic preconditioning does not prolong surgery since it can be done while preparing the liver for resection. 11 The report by Ito et al 34 reinforces the general point that preconditioning is a promising approach for preventing reperfusion injury. It will be important to learn more about the molecular mechanisms involved, towards developing safer and more effective methods of exploiting its clinical benefit.…”
mentioning
confidence: 83%
See 4 more Smart Citations
“…In the case of major hepatectomy performed under inflow occlusion, the technique of ischemic preconditioning does not prolong surgery since it can be done while preparing the liver for resection. 11 The report by Ito et al 34 reinforces the general point that preconditioning is a promising approach for preventing reperfusion injury. It will be important to learn more about the molecular mechanisms involved, towards developing safer and more effective methods of exploiting its clinical benefit.…”
mentioning
confidence: 83%
“…37 Based on this indirect evidence, Yamamoto et al 35 suggested that the administration of doxorubicin before liver surgery may improve postoperative liver function in addition to the desired chemotherapeutic effects. Ito et al 34 extended these early findings by examining the involvement of HO-1.…”
mentioning
confidence: 91%
See 3 more Smart Citations